Second Teachers’ Training Workshop: Feedback of the Participant Faculty Members - Piryani, Rano Mal; Piryani, Suneel; Gautam, Narayan (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Teachers training is amongst the faculty development programs that facilitates in acquiring, and updating educational skills, thereby improving teaching learning practices. Universal College of Medical Sciences (UCMS) Bhairahawa, Nepal organized second teachers training workshop in September 8-13, 2019. The objective of this study was to seek the immediate reaction of the participant faculty members and assess it MATERIAL AND METHODS: The valid semi-structured questionnaire was used for taking feedback of the participants. The questionnaire was composed of four parts: A) demographic information, B) overall feedback on training workshop, C) feedback on specific group of sessions and D) Feedback regarding strengths, area for improvement, immediate impact and application in practice. Data was analyzed using SPSS version 21. RESULTS: The participants rated training on scale 1-10 (1=poor, 10=excellent) regarding its usefulness (7.88±1.58), content (7.44±1.55), relevance of session & content (7.69±1.49), facilitation (7.25± 1.69) and training as overall (7.94± 1.44). The rating was notable. The rating on Likert scale 1-4 (1= not important, 4= extremely important) for “sessions on curriculum” (3.38±0.50), “sessions on teaching/learning methods” (3.25±0.68), “sessions on PBL” (3.06±0.68), “sessions on microteaching” (3.56±0.51) and sessions on assessment (3.19±0.75) was also remarkable. All participants strongly agreed (4.00±0.0), training has transformed them as better educator. The participants shared adequate content delivered systematically, group work exercises were best resources, and resource persons were friendly and competent, and suggested to reduce time of training and include more group work. Almost all participants except one perceived training has enormous impact on them academically, professionally and personally and all committed what’s learnt/acquired will apply in practice. CONCLUSION: Overall, reaction of the participants was constructive and they acknowledged the importance of training and agreed training has transformed them as better educators. Almost all participants perceived training has immense impact on them academically and they committed what’s learnt will apply in practice.